Palaeoceanographic development in Leirdjupet Trough, western Barents Sea, during the Holocene: evidence from foraminiferal, isotopic and sedimentological records - Kovalenko, Boriss (UiT Norges arktiske universitet, 2015)
The gravity core HH14-012GC from Leirdjupet Trough has been investigated to detect changes in sedimentation and the variations in distribution patterns of marine microorganisms (Planktic and Benthic Foraminifera) and stable isotope values of their shells to reconstruct the variability of the inflow of Atlantic water to the study area. The results are compared to published paleodata records to investigate regional paleoceanographic processes in western Barents Sea and Svalbard region. Analyses of sediment core HH14-012GC show that Atlantic water has continuously been present in the study area during the last 11,000 years. The dominant benthic species during the Holocene transition indicate glaciomarine environmental conditions and strong influence of Polar water. During the early Holocene a significant increase of Atlantic Water inflow into Leirdjupet Trough occurred. In the interval c. 10 – 9 ka BP a rapidly increasing flux of benthic and planktic foraminifera, dominance of the benthic foraminiferal species Cassidulina neoteretis, and low of δ18O values represent the Holocene temperature optimum at the study area and the strongest warm Atlantic water inflow for the Holocene. The mid-Holocene (8.3 – 4 ka BP) represents a transition period with relative stable environmental conditions. Increasing deposition of IRD indicates sea ice and icebergs arriving at the core site and is probably related to decrease in sea surface temperature. In the late Holocene climatic conditions became cooler. The dominant benthic species Cassidulina reniforme and Islandiella norcrossi indicate cooling of the bottom water. The dominance of Neogloboquadrina pachyderma sinistral (s) and Turborotalia quinqueloba with increasing trend of N. pachyderma sinistral (s) is related to the continuous decreasing of surface water temperature in the area. The decreasing trend in temperature continues during the late Holocene and the influence of Atlantic water in the area diminished further.